A case of indeterminate dendritic cell tumor presenting with leonine facies. (11th September 2015) - Oh, Chee Won; Ivan, Doina; Curry, Jonathan L.; Ellis, Rachel; Gerber, Howard; Duvic, Madeleine; Torres‐Cabala, Carlos
Abstract : Background: Indeterminate dendritic cell tumor is an extremely rare neoplastic proliferation of dendritic cells that share immunophenotypic features of Langerhans cells and macrophages but lack Birbeck granules and Langerin expression. Methods: We report a 55‐year‐old female presenting with a leonine facies and generalized multiple confluent papules, nodules and plaques on neck, upper trunk, arms and thighs. Laboratory evaluations were performed including skin biopsies, peripheral blood flow cytometry and positron emission tomography–computed tomography. Results: The lesional skin biopsy showed a dense dermal and perifollicular infiltrate composed of histiocytoid cells with nuclear grooves lacking dendritic processes in a background of lymphocytes. Eosinophils were absent. The histiocytoid cells were CD68+CD1a+Langerin− and only focally S100+. Special stains including GMS, Gram and Fite were all negative for infectious organisms. Although an initial diagnosis suggesting Langerhans cell histiocytosis was proposed due to CD1a positivity, a diagnosis of indeterminate dendritic cell tumor was finally rendered based on the histopathological findings and the lack of expression of Langerin. Conclusion: This case illustrates the variegated clinical presentation of indeterminate cell tumor and the necessity of appropriate immunohistochemical workup for its diagnosis.